Sistem Perhitungan Estimasi SPP pada SMAN 1 Cibungbulang Berbasis Web Dengan Menggunakan Metode ABC (Activity Based Costing) - Munajir, Kayum; Kamilah, Nurul; Gerhana, Gerhana (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
This study aims to develop a web-based SPP estimation system using the Activity Based Costing (ABC) method in school administration. In the context of increasing educational costs, the ABC approach offers a solution for managing costs efficiently and transparently. Quantitative data, such as SPP rates, are used in this study to calculate the precise costs in developing the system. Although speculative, this system is expected to enhance educational services by providing more timely and accurate information, as well as promoting the adoption of innovative cost management methods in other educational institutions. The implementation of a web-based information system with the ABC method at SMAN 1 Cibungbulang is considered efficient, transparent, and improves cost accuracy, thus providing more accurate information. The analysis results show that the SPP costs in 2023 originated from the total unit level-costs (5 activities), plant-level costs (2 activities), and product-level costs (1 activity), each producing Rp. 6,043,166, Rp. 23,005, and Rp. 2,445 per unit, totaling Rp. 6,068,666 per year or Rp. 505,722 per month. Additionally, the activity cost burden on products reached Rp. 193,431,640 per year. This study contributes to a deeper understanding of ABC implementation in the education.